Enhancing Digital Business Students Competence through UI/UX Design Training for Digital Product Development - Lista Meria; Michael Surya Gunawan; Solahudin Solahudin; Untung Rahardja; Aroha Patel (ADI Pengabdian Kepada Masyarakat, 2026)
Rapid digital transformation requires digital business students to possess practical competencies in User Interface (UI) and User Experience (UX) design as a fundamental basis for developing user-oriented digital products. However, learning processes that are still dominated by theoretical approaches often limit students readiness to apply UI/UX principles in an applicative and contextual manner. This community service activity aims to enhance conceptual understanding and practical UI/UX design skills among digital business students through training that is simple, applicable, and practice-based. The program was implemented using a participatory approach through training and workshops, which included the presentation of basic UI/UX concepts, demonstrations of digital design tools, interactive discussions, and hands-on practice in developing wireframes and digital product prototypes. The effectiveness of the program was evaluated through pre-tests, post-tests, and assessments of participants’ design outputs. The results of the activity indicate a significant improvement in students’ understanding of UI/UX concepts, interface design capabilities, and confidence in developing digital product prototypes. Participants were able to apply user-centered design principles in a more systematic, logical, and useroriented manner. In conclusion, this UI/UX design training program effectively strengthened the digital competencies of digital business students and enhanced their readiness to face the demands of the digital industry. The program also highlights the importance of practice-based learning in developing innovative, adaptive, and competitive human resources in the digital economy era.